Short Forms of the Cross-Cultural (Chinese) Personality Assessment Inventory: Reliability, Validity, and Measurement Invariance Across Gender - Zhou, Mingjie; Huang, Duan; Ren, Fen; Fan, Weiqiao; Mu, Weiqi; Li, Fugui; Zhang, Jianxin; Cheung, Fanny M. (Frontiers in Psychology, 2021)
Filling out long questionnaires can be frustrating, unpleasant and discouraging for respondents to continue. This is why shorter forms of long instruments are preferred, especially when they have comparable reliability and validity. In present study, two short forms of the Cross-cultural (Chinese) Personality Assessment Inventory (CPAI-2) were developed and validated. The items of the short forms were all selected from the 28 personality scales of the CPAI-2 based on the norm sample. Based on some priori criteria, we obtained the appropriate items and constructed the 56-item CPAI and the 28-item CPAI. Then, we examined the factor structure of both short forms with ESEM and replicated the four-factor structure of the original CPAI-2, reflecting the four personality domains of Chinese people, namely, Social Potency, Dependability, Accommodation, and Interpersonal Relatedness. Further analyses with ESEM models demonstrate full measurement invariance across gender for both short forms. The results show that females score lower than males on Social Potency. In addition, these four factors of both short forms have adequate internal consistency, and the correlation patterns of the four factors, the big-five personality traits and several health-related variables are extremely similar across the two short forms, reflecting adequate and comparable criterion validity, convergent validity and discriminant validity. Overall, the short versions of CPAI-2 are psychometrically acceptable and have practically implications for measuring Chinese personality and cross-cultural research.